Campaña de lanzamiento para la marca flying tiger copenhagen en el mercado peruano - Zegarra Carbajal, Estefany Nicole (2022)
In Perú, the retail sector has grown considerably from 2016 to the present. So much so, that the Danish brand Flying Tiger Copenhagen plans to open its stores in the country in the main shopping centers of the capital and offer a wide range of products for the home, toys, stationery, technology, among others. Therefore, this work develops the comprehensive launch campaign for the brand, where all marketing and communication efforts are focused on the digital channel, television and outdoor advertising. The objective of this work is to generate brand awareness and brand recall among young adults between 17 and 30 years of age in metropolitan Lima, Arequipa and Trujillo. In this way, it is identified that the strategic launching concept is the following: ''We turn the ordinary into something extraordinary''; where the detected insight of the target is ''I want products with innovative and affordable designs, to brighten my days; however, I do not find authentic products that are economical'' and the differential value of Flying Tiger Copenhagen focuses on the fact that it does not design products to look good, it designs them to make people feel good.